2012
DOI: 10.1038/npp.2012.137
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a microRNA MIR137 Susceptibility Variant on Brain Function in People at High Genetic Risk of Schizophrenia or Bipolar Disorder

Abstract: A recent 'mega-analysis' combining genome-wide association study data from over 40 000 individuals identified novel genetic loci associated with schizophrenia (SCZ) at genome-wide significance level. The strongest finding was a locus within an intron of a putative primary transcript for microRNA MIR137. In the current study, we examine the impact of variation at this locus (rs1625579, G/T; where T is the common and presumed risk allele) on brain activation during a sentence completion task that differentiates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 67 publications
5
66
1
Order By: Relevance
“…The analysis of the relationship between rs1625579 genotypes and miR-137 expression in the postmortem DLPFC revealed a significantly lower miR-137 expression level in the homozygous TT subjects compared to TG and GG subjects in the control group [82]. Moreover, homozygous TT individuals at high genetic risk for schizophrenia exhibited a lower activation in the posterior right medial frontal gyrus compared to healthy controls after a sentence completion task that differentiates individuals with schizophrenia and their relatives from controls [83]. Further studies demonstrated that the risk variant rs1625579 might substantially influence phenotypic variability in schizophrenia, with the miR-137 risk genotype Table 1 The miRNA abnormalities in schizophrenia and bipolar disorder patient brain tissues…”
Section: Mirnas In Schizophrenia: Results From Human Studiesmentioning
confidence: 98%
“…The analysis of the relationship between rs1625579 genotypes and miR-137 expression in the postmortem DLPFC revealed a significantly lower miR-137 expression level in the homozygous TT subjects compared to TG and GG subjects in the control group [82]. Moreover, homozygous TT individuals at high genetic risk for schizophrenia exhibited a lower activation in the posterior right medial frontal gyrus compared to healthy controls after a sentence completion task that differentiates individuals with schizophrenia and their relatives from controls [83]. Further studies demonstrated that the risk variant rs1625579 might substantially influence phenotypic variability in schizophrenia, with the miR-137 risk genotype Table 1 The miRNA abnormalities in schizophrenia and bipolar disorder patient brain tissues…”
Section: Mirnas In Schizophrenia: Results From Human Studiesmentioning
confidence: 98%
“…and qRT-PCR validation and discovered just one miRNA, miR29c, to be upregulated. The SNP rs1625579, which affects miR-137 in SZ, was also found to be functionally associated with individuals at risk of BD (45).…”
Section: Bdmentioning
confidence: 96%
“…Mega-analysis has advantages over meta-analysis in that datasets can be combined to enhance statistical power, permitting examination of hypotheses that cannot be tested within single studies. This approach has been used to combine datasets in areas such as genetics (Whalley et al, 2012), functional neuroimaging (Hallahan et al, 2011), and psychiatric treatment (de Maat et al, 2008;Thase et al, 1997). The current study used the combined dataset to address three novel goals: (1) to test the direct versus indirect (mediated by autobiographical belief) effects of suggestion on suggestion-related preferences and behavior intention; (2) to examine the impact of the development (x), which in turn influence behavior (y).…”
Section: Introductionmentioning
confidence: 99%